Evaluation of a Combination of Waveform Amplitude and Peak Latency in Intraoperative Spinal Cord Monitoring. Issue 17 (1st September 2018) - Kobayashi, Kazuyoshi; Ando, Kei; Shinjo, Ryuichi; Ito, Kenyu; Tsushima, Mikito; Morozumi, Masayoshi; Tanaka, Satoshi; Machino, Masaaki; Ota, Kyotaro; Ishiguro, Naoki; Imagama, Shiro
Abstract : Study Design: Retrospective study. Objective: The goal of the study was to investigate the significance of a change in latency in monitoring of transcranial muscle-action potential (Tc-MsEP) waveforms. Summary of Background Data: Tc-MsEP has become a common approach in spine surgery due to its sensitivity and importance in motor function. Many reports have defined the alarm point of Tc-MsEP waveform as a particular decrease in amplitude, but evaluation of the waveform latency has not attracted as much attention. Methods: The subjects were 70 patients who underwent spine surgery using intraoperative Tc-MsEP monitoring. The peak latency was defined as the period from stimulation until the waveform amplitude reached its peak. Relationships with postoperative paralysis were examined separately for latency delays of 5% or more and 10% or more, and in combination with a decrease in amplitude of 70% or more from baseline. Results: Acceptable baseline Tc-MsEP responses were obtained from 1225 of 1372 muscles in the extremities (89.3%). Seven of the 70 patients (10%) had postoperative paralysis. A decrease in intraoperative amplitude of 70% or more from baseline occurred in 25 cases, with sensitivity 100%, specificity 71%, false positive rate 29%, and positive predictive value (PPV) 28% for prediction of postoperative paralysis. Compared to baseline, 15 cases had a latency delay of 5% or more, which gave a sensitivity of 100%, specificity of 87%, false positive rate of 0%, and PPV 47%, and 8 cases had a delay of 10% or more, which gave a sensitivity of 86%, specificity of 97%, false positive rate of 3%, and PPV 75%. A combination of a decrease in amplitude of 70% or more from baseline and a delay in latency of 10% or more from baseline had a sensitivity of 86%, specificity of 98%, and a false positive rate of 2%, and PPV 86%. Conclusion: Combined use of latency and amplitude could lead to reduction of false positives and increase of PPV in Br(E)-MsEP monitoring. Level of Evidence: 3